Building resilient crop-livestock farming systems in Senegal - Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Senegalese agricultural and livestock sector is the main economic activity representing approximately 17% of the gross domestic product (GDP) and employing 70% of the population. Around 350,000 families nationwide carry out livestock breeding activities, representing nearly 30% of Senegalese farmers. Limited agricultural production conditions, characterized by poor soils and weather conditions, limited access to advisory services, and poor-quality agricultural inputs and insufficient infrastructure contribute to Senegal’s inability to satisfy its food needs. Consequently, the country depends on food imports.